CAMPAIGN AGAINST FAST FASHION AS AN IDEOLOGICAL CONSTRUCTION OF ENVIRONMENTAL RESPONSIBILITY: A CRITICAL DISCOURSE ANALYSIS - Alvintia Asri Mariskandari; Evi Jovita Putri (IdeBahasa, 2026)
This study aimed to analyze the construction of ideological meaning related to sustainability and consumption in Josephine Philip’s speech entitled “The Simple Solution to Fast Fashion.” The data source of this research was the transcript of the speech, which was examined using Teun A. van Dijk’s Critical Discourse Analysis framework. This study employed a descriptive qualitative method; the data were collected through observation and transcription, and were analyzed using content analysis focusing on macrostructure, superstructure, and microstructure. The findings revealed that the speech constructed fast fashion as a global environmental crisis through three interconnected ideological themes: global waste impact, individual responsibility in garment repair, and a call to action. At the macro level, the thematic focus reframed fast fashion from a lifestyle issue into an urgent ecological concern; at the superstructural level, the speech was coherently organized from personal narrative to global consequences and persuasive solutions; and at the microstructural level, semantic emphasis, syntactic coherence, lexical repetition, pronoun variation, and rhetorical strategies reinforced ideological meaning and guided audience interpretation. Overall, the speech functioned not only as informative discourse but also as an ideological intervention that shaped social cognition and encouraged sustainable behavior, and future research is recommended to explore similar environmental speeches in different contexts to enrich discourse studies on sustainability.